2017
DOI: 10.1371/journal.pone.0177540
|View full text |Cite
|
Sign up to set email alerts
|

Structural models of the different trimers present in the core of phycobilisomes from Gracilaria chilensis based on crystal structures and sequences

Abstract: Phycobilisomes (PBS) are accessory light harvesting protein complexes that directionally transfer energy towards photosystems. Phycobilisomes are organized in a central core and rods radiating from it. Components of phycobilisomes in Gracilaria chilensis (Gch) are Phycobiliproteins (PBPs), Phycoerythrin (PE), and Phycocyanin (PC) in the rods, while Allophycocyanin (APC) is found in the core, and linker proteins (L). The function of such complexes depends on the structure of each component and their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Together with the above, the spectrum observed under denaturing conditions corresponds to that of the αβ heterodimer, which is not affected under the conditions tested [35] . When analyzing the contact surfaces and interactions that stabilize the trimeric structure of APC, an average area of 500 Å 2 with 8 hydrogen bonds and 2 contact salt bridges between each pair of heterodimers can be observed [38] .
Fig.
…”
Section: Structural Characteristics Of Pbpsmentioning
confidence: 99%
“…Together with the above, the spectrum observed under denaturing conditions corresponds to that of the αβ heterodimer, which is not affected under the conditions tested [35] . When analyzing the contact surfaces and interactions that stabilize the trimeric structure of APC, an average area of 500 Å 2 with 8 hydrogen bonds and 2 contact salt bridges between each pair of heterodimers can be observed [38] .
Fig.
…”
Section: Structural Characteristics Of Pbpsmentioning
confidence: 99%
“…Both GpPBS core and PpPBS core are characterized by two unique features: lack of one trimeric ApcA/B disc at the distal end of ApcD in each basal cylinder ( Fig. 1A ) and thus a decreased copy number (by comparing to a four-Apc-trimer cylinder) of ApcC (Apc C; formerly L C ), a small polypeptide linker protein that stabilizes and caps each end of the core cylinders ( 20 , 21 ). The top cylinder in both GpPBS core and PpPBS core is featured by two Apc trimers, instead of four.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews (from 2016 onwards) pertaining to PE are yet scarce, but existent (and discussed together with other PBP), and they seem to be more focused on those obtained from microalgae [4,9,17,19,32,55,106]. These include pigment availability and utilization [9], PBP/PBS structural chemistry [1,27,32,107], production [1,17,19,55], purification [19], and applications [1,4,19,32,62,106]. Recently, Zhang et al [108] uncovered the entire PBS complex (to 3.5 Å) from the red seaweed Griffithsia pacifica, through Cryogenic Electron Microscopy (cryo-EM).…”
Section: Phycoerythrinmentioning
confidence: 99%
“…Research into APC seems to be yet quite scarce when compared with research targeted on the other PBP found in red seaweeds, and it seems to be more focused on understanding mechanisms of structure [107,141,142] and synthesis [33,143]. Nevertheless, regarding extraction methods, diethyl ether gave good results, but methanol and ethanol were deemed improper in APC extraction of Furcelaria lumbricalis [74].…”
Section: Allophycocyaninmentioning
confidence: 99%